Comparison of PI and PID Controlled Bidirectional DC-DC Converter Systems - K.C. Ramya; V. Jegathesan (Institute of Advanced Engineering and Science, 2016)
This paper deals with comparison of responses of the PI and the PID controlled bidirectional DC-DC converter systems. A coupled inductor is used in the present work to produce high gain. Open loop and closed loop controlled systems with PI and PID controllers are designed and simulated using Matlab tool. The principles of operation and simulation case studies are discussed in detail. The comparison is made in terms of rise time, fall time, peak overshoot and steady state error.